Farmer participation in supermarket channels and technical efficiency: The case of vegetable production in Kenya - Elizaphan J.O. Rao; Matin Qaim (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2009)
Supermarkets and high-value exports are currently gaining ground in the agri-food systems of many developing countries. While recent research has analyzed income effects in the small farm sector, impacts on farming efficiency have hardly been studied. Using a survey of Kenyan vegetable growers and a stochastic frontier approach, we show that participation in supermarket channels increases mean technical efficiency by 19%. This gain is bigger at lower levels of efficiency, suggesting the potential for positive income distribution effects. However, disadvantaged farms often have problems in meeting strict supermarket requirements. Innovative market linkage initiatives can increase the probability of participation significantly.
Keywords: Q12; O12; O13; D24; 330; supermarkets; small farms; technical efficiency; stochastic frontier; sample selection; Kenya